Pemanfaatan Biji Nangka Dan Kulit Kacang Tanah Sebagai Bahan Baku Bioplastik Dengan Penambahan Gliserol - Aeni, Nurul; , Dra. Aminah Asngad M.Si (2017)
Human life cannot be separated from the problem of garbage, especially plastic trash types that are non-biodegradable or plastic is not degraded by the activity of microorganisms that cause the accumulation of garbage and environmental damage. Therefore, to accelerate the rate of degradation in the manufacture of plastics replace natural materials such as jackfruit seed starch because it is easily degraded, abundant and underutilized. To improve the mechanical properties of starch adding the peanuts leather and glycerol. The purpose of this study is to examine the quality of bioplastics from jackfruit seeds with the addition of peanut shells and glycerol parameters of tensile resistance, elongation at break and biodegradability properties. This study used an experimental method completely randomized design (CRD) factorial design. The first factor is the mass ratio of jackfruit seed flour and peanut skins (N), N1 = 8.5: 1.5G, N2 = 9: 1g, and N3 = 9.5: 0,5g and second factor is the volume of glycerol used (G), G1 = 6ml, 7ml = G2, G3 = 8ml. The results showed that the highest tensile strength at treatment N1G1 = 2.08 N / mm2 and for elongation at break of the highest in the treatment N1G3 = 33.33%. The highest biodegradability test results in treatment N2G2 biggest degraded as much as 78.826%. Keywords: Bioplastic, Biodegradable, Jackfruit Seeds, Peanuts Leather, Glycerol